2020
DOI: 10.1111/lasr.12456
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguring the Deserving Refugee: Cultural Categories of Worth and the Making of Refugee Policy

Abstract: Studies on asylum give little explanatory power to the role of categories of worth in how lawmakers formulate asylum law in lack of a clear policy framework for determining eligibility for asylum status. This article contends that during periods of policy upheaval, distinctions of worth shift to forefront lawmaking: lawmakers renegotiate the moral boundaries between categories of deserving and undeserving refugees to give content in ambiguous law. In the United States, lawmakers drew on the concept of immutabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Overall, our analysis has shed light on how notions of deservingness (Chauvin and Garcés-Mascareñas, 2014) permeate society on the migration issue in ambivalent ways, especially in unsettled times (Shiff, 2020). Far from being consensual and stable over time, we have argued that deservingness – and the moral judgements it relates to – is constantly negotiated and re-interpreted not only by state, legal and charity actors (Chauvin and Garcés-Mascareñas, 2014; Shiff, 2020) but also by the individuals operating in the field. We have shown that the focus on how individual actors cope with moral and emotional dilemmas in the course of their engagement is crucial for the understanding of collective action, during which participants re-assess their motivations, their emotions and the meaning given to their practices.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, our analysis has shed light on how notions of deservingness (Chauvin and Garcés-Mascareñas, 2014) permeate society on the migration issue in ambivalent ways, especially in unsettled times (Shiff, 2020). Far from being consensual and stable over time, we have argued that deservingness – and the moral judgements it relates to – is constantly negotiated and re-interpreted not only by state, legal and charity actors (Chauvin and Garcés-Mascareñas, 2014; Shiff, 2020) but also by the individuals operating in the field. We have shown that the focus on how individual actors cope with moral and emotional dilemmas in the course of their engagement is crucial for the understanding of collective action, during which participants re-assess their motivations, their emotions and the meaning given to their practices.…”
Section: Resultsmentioning
confidence: 94%
“…As shown by Chauvin and Garcés-Mascareñas (2014), the notion of ‘deservingness’ is useful as it allows us to explore how migrants’ strategies intersect with state definitions of legal categories and how different agents (e.g. charities, street-level bureaucrats) define and implement processes of distinction between groups of migrants (Dhaliwal and Forkert, 2015; Menjívar and Lakhani, 2016; Monforte et al, 2019; Shiff, 2020; Tonkiss, 2018). However, only a few studies have explored this idea from the point of view of the individual actors who engage in volunteering.…”
Section: Introductionmentioning
confidence: 99%
“…The discussion over “who deserves” the allegedly unconditional good of human rights is a reflection and a means of sustaining the actuarial penology in its broad sense, that does not only classify groups of people by their “dangerousness” but also translates these moral classifications into varying levels of desert. Perceptions of worthiness are constructed by screening out information that does not respond to pre-established moral classifications (Shiff, 2020 ).…”
Section: Theoretical Analysis Of Legislation and Policies Toward Ass ...mentioning
confidence: 99%
“…The importance of political asylum has faded, in favor of claims based on humanitarian and medical considerations, chiefly, physical illness, and the role of seemingly objective biomedical factors has grown (Fassin, 2005; Lakhani & Timmermans, 2014; Ticktin, 2011). As migrants and their attorneys carefully devise strategies to expand and challenge formal legal categories, they sometimes encounter flexibility in state determinations, partly because of the discretion around and indeterminacy of immigration law (Galli, 2020; Kim, 2011; Shiff, 2020; Vogler, 2016). At the same time, humanitarian relief in the United States remains restrictive and formal eligibility criteria narrow.…”
Section: Literature Reviewmentioning
confidence: 99%